Real estate investment : strategy analysis, decisions - Pyhrr, Stephen A.; Cooper, James R.; . (J. Wiley, 1989)
Real estate investment: the state of the art. Systematic investment analysis. Analyzing real estate markets under changing conditions. Negotiations, management, and termination decisions. Porfolio strategy and investment outlook. Property selection.